Upaya Keluarga Mencegah Penularan Tuberkulosis - Suprajitno Suprajitno; Sri Mugianti; Umi Albaqiyatus Sholikhah (STIKes Patria Husada Blitar, 2015)
Tubercolusis is an infection disease that can prevented through the family effort. The studyÂ purpose was to describe the family effort to prevent transmission of tuberculosis. This study was descriptive. The study population was all of family who have family members suffering of tuberculosis wasÂ record in UPTD Kesehatan Kota Blitar as many as 36 families. The sample used total population. Collecting data using questionnaires. The questionnaire filled in by family members who care for and assist the patient every day. The results showed 6% of the family effort of prevention were better category, 36% of the family effort of prevention were enough category, and 58% of the family effort of prevention were less category. Less family efforts prevention showed were that do not shut your mouth when coughing, coughing does not turn heads, discard sputum by not hoarded, not given a sputum container with liquid soap (disinfectant), and sputum container is not closed. The family efforts not supported to prevent were not drying mattress least once a week, family members not consume healthy foods, and a little consume of vitamin C. Recommended were UPTD Kesehatan Kota Blitar to provide health education of transmission Tuberculosis in the family and the improved health status of the family.